β2-spectrin depletion impairs DNA damage repair - Horikoshi, Nobuo (Oncotarget, 2016)
β2-Spectrin (β2SP/SPTBN1, gene SPTBN1) is a key TGF-β/SMAD3/4 adaptor and transcriptional cofactor that regulates TGF-β signaling and can contribute to liver cancer development. Here we report that cells deficient in β2-Spectrin (β2SP) are moderately sensitive to ionizing radiation (IR) and extremely sensitive to agents that cause interstrand cross-links (ICLs) or replication stress. In response to treatment with IR or ICL agents (formaldehyde, cisplatin, camptothecin, mitomycin), β2SP deficient cells displayed a higher frequency of cells with delayed γ-H2AX removal and a higher frequency of residual chromosome aberrations. Following hydroxyurea (HU)-induced replication stress, β2SP-deficient cells displayed delayed disappearance of γ-H2AX foci along with defective repair factor recruitment (MRE11, CtIP, RAD51, RPA, and FANCD2) as well as defective restart of stalled replication forks. Repair factor recruitment is a prerequisite for initiation of DNA damage repair by the homologous recombination (HR) pathway, which was also defective in β2SP deficient cells. We propose that β2SP is required for maintaining genomic stability following replication fork stalling, whether induced by either ICL damage or replicative stress, by facilitating fork regression as well as DNA damage repair by homologous recombination.